Gastric antral vascular ectasia in a patient with lupus undergoing hemodialysis: a case report - Kang, Seok Hui (BMC Nephrol, 2020)
BACKGROUND: Gastric antral vascular ectasia (GAVE), associated with autoimmune diseases, such as systemic lupus erythematosus, and hepatic or renal disorders, is a rare cause of gastrointestinal bleeding. We report the case of a patient with lupus erythematosus undergoing hemodialysis with an uncorrectable anemia caused by GAVE. CASE PRESENTATION: A 76-year-old Korean woman with lupus undergoing hemodialysis frequently complained of symptoms or signs associated with anemia, such as dizziness, dyspnea, hypotension, melena, and hematemesis. Gastrointerstinal endoscopy revealed multiple erythematous and hyperemic mucosal lesions at the distal antrum without active bleeding, a finding compatible with GAVE. Although she frequently complained of symptoms or signs associated with anemia and had frequent gastrointestinal endoscopies with or without pre-emptive argon plasma coagulation, her clinical status is relatively stable, and she is undergoing maintenance hemodialysis without anticoagulants. CONCLUSION: This clinical case suggests that GAVE should be considered as a cause of the anemia resistant to erythropoiesis-stimulating agents and iron supplementation in patients with chronic kidney disease and lupus.